A Nonlinear Empirical Analysis of Oil Price Co-movements - Coronado, Semei; Fullerton, Thomas M.; Rojas, Omar (International Journal of Energy Economics and Policy, 2018)
Nonlinear co-movements are analyzed for the daily returns calculated for Brent and West Texas Intermediate (WTI) crude oil prices. The sample period includes data for the pre-2008 price increases and the post-2014 price declines. Empirical results obtained indicate that it is important to allow for nonlinear and asymmetric patterns in the data. After doing so, unidirectional causality from Brent to WTI is documented with price declines exerting more reliable effects than price gains. That is in contrast to what has been documented for other sample periods that do not allow for potential nonlinear and asymmetric linkages. Keywords: Nonlinear tests; Co-movement; Crude oil prices, Granger causality. JEL Classifications: C32, G15, Q43